Combined multimodal ctDNA analysis and radiological imaging for tumor surveillance in Non-small cell lung cancer - Martin Metzenmacher (Elsevier, 2022)
Background: Radiology is the current standard for monitoring treatment responses in lung cancer. Limited sensitivity, exposure to ionizing radiations and related sequelae constitute some of its major limitation. Non-invasive and highly sensitive methods for early detection of treatment failures and resistance-associated disease progression would have additional clinical utility. Methods: We analyzed serially collected plasma and paired tumor samples from lung cancer patients (61 with stage IV, 48 with stages I-III disease) and 61 healthy samples by means of next-generation sequencing, radiological imaging and droplet digital polymerase chain reaction (ddPCR) mutation and methylation assays. Results: A 62% variant concordance between tumor-reported and circulating-free DNA (cfDNA) sequencing was observed between baseline liquid and tissue biopsies in stage IV patients. Interestingly, ctDNA sequencing allowed for the identification of resistance-mediating p.T790M mutations in baseline plasma samples for which no such mutation was observed in the corresponding tissue. Serial circulating tumor DNA (ctDNA) mutation analysis by means of ddPCR revealed a general decrease in ctDNA loads between baseline and first reassessment. Additionally, serial ctDNA analyses only recapitulated computed tomography (CT) -monitored tumor dynamics of some, but not all lesions within the same patient. To complement ctDNA variant analysis we devised a ctDNA methylation assay (methcfDNA) based on methylation-sensitive restriction enzymes. cfDNA methylation showed and area under the curve (AUC) of > 0.90 in early and late stage cases. A decrease in methcfDNA between baseline and first reassessment was reflected by a decrease in CT-derive tumor surface area, irrespective of tumor mutational status. Conclusion: Taken together, our data support the use of cfDNA sequencing for unbiased characterization of the molecular tumor architecture, highlights the impact of tumor architectural heterogeneity on ctDNA-based tumor surveillance and the added value of complementary approaches such as cfDNA methylation for early detection and monitoring